Evaluating the Impact of Demographic Covariates on Healthcare Access and NCD Risk: Evidence from a Cross-Sectional Survey in Five Arab Countries - Elkhouli, Mohamed Ahmed (International Journal of Statistics in Medical Research, 2026)
This study evaluated how demographic factors and socio-economic factor influence on the healthcare access and non-communicable disease (NCD) risk in the five different Arab countries. It has also investigating how Gender moderates this relationship. It has used quantitative cross-sectional design where data was collected from 400 respondents in Egypt, Saudi Arabia, Jordan, Morocco and the United Arab Emirates. The data was analysed using binary logistic regression and chi-square tests. The results indicated considerable variation across countries in terms of access to health care and NCD risk. In the access to health care services category, the highest frequency was observed in the UAE and Morocco, whereas the lowest frequency was recorded in Egypt and Saudi Arabia. With regard to NCD risk, the highest and lowest frequencies were observed in Egypt and Saudi Arabia and the UAE and Morocco, respectively. The logistic regression indicated that factors such as age, residence, education, employment status, income level, housing arrangements, and assets ownership had significant impacts on access to healthcare services and NCD risk. Factors like age positively influenced access to health services and NCD risk while education, high-income levels, and assets ownership negatively impacted NCD risk. Even though the effect of gender was directly influenced by the two health variables, moderation analysis revealed that gender did not influence the relationship between them. The study has highlighted importance of socioeconomic determinants in shaping health outcomes across Arab countries and suggests that policies aimed to improve education, economic conditions and healthcare accessibility are effective in reducing NCD risk and promoting equal healthcare access than gender specific intervention alone. Hence, this study neglects the theoretical norm of gender differences and rather indicates that other SES factors can be evaluated for having a moderating role in this regards.